The Performance Mindset : 7 Steps to Success in Sport and Life. - Klarica, Anthony J. (John Wiley & Sons, Incorporated, 2022)
Build your resilience -- Step 3 Sharpen your focus -- Self-talk: you are what you think -- 'The little voice' -- Technical, tactical and emotional self-talk -- Positive, negative or neutral and curious self-talk -- Mantras -- Internal or external focus -- Narrow or broad: switching focus -- Getting in the zone or flow -- Self-regulation -- Distractions -- Secondary errors -- Being in the present -- Attention to detail -- Focus on what you can control -- Visual and physical cues -- Body language -- Use of time -- Chunking and race plans -- The Tan -- Adopting and adapting a plan -- Routines and clarity -- Summary -- Build your focus -- Step 4 Champion your leadership -- Diamonds: leadership by example -- Influence -- The what and the how of leadership -- Leading self -- Leading culture -- Leading others -- Leading situations -- Leading structure and systems -- Leadership growth -- Formal and informal leadership -- Leadership density -- Leadership groups -- Captain class -- Leadership qualities -- Contributor -- Sport integrity -- Team and others focus -- Communication -- Determination -- Composure -- Positive performer -- Self-belief -- Summary -- Build your leadership -- Step 5 Foster your culture -- Culture in practice -- Thinking, decisions and behaviour -- High-performance environments -- Individual athlete and coach influence on culture -- Cultural consistency -- Psychological safety -- Learn and grow -- Emotional intelligence -- Relationships and communication -- Mastery climate -- The New Zealand All Blacks -- Building culture -- Terminology and engagement -- Clear values and behaviours described -- Support people and performance -- Leaders live, model and drive culture -- Coaching, celebrating and accountability -- Display and share -- Integrate into processes -- Monitoring and evolving culture with data and measurement.